Supplemental Light-Emitting Diode Inter-Lighting Increases Tomato Fruit Growth Through Enhanced Photosynthetic Light Use Efficiency and Modulated Root Activity - Paponov, Martina; Kechasov, Dmitry; Lacek, Jozef; Verheul, Michel J.; Paponov, Ivan A. (Frontiers in Plant Science, 2020)
We investigated the effect of supplemental LED inter-lighting (80% red, 20% blue; 70 W m−2; light period 04:00–22:00) on the productivity and physiological traits of tomato plants (Flavance F1) grown in an industrial greenhouse with high pressure sodium (HPS) lamps (235 W m−2, 420 µmol m−2 s−1 at canopy). Physiological trait measurements included diurnal photosynthesis and fruit relative growth rates, fruit weight at specific positions in the truss, root pressure, xylem sap hormone and ion compositions, and fruit quality. In the control treatment with HPS lamps alone, the ratio of far-red to red light (FR:R) was 1.2 at the top of the canopy and increased to 5.4 at the bottom. The supplemental LED inter-lighting decreased the FR:R ratio at the middle and low positions in the canopy and was associated with greener leaves and higher photosynthetic light use efficiency (PLUE) in the leaves in the lower canopy. The use of LED inter-lighting increased the biomass and yield by increasing the fruit weight and enhancing plant growth. The PLUE of plants receiving supplemental LED light decreased at the end of the light period, indicating that photosynthesis of the supplemented plants at the end of the day might be limited by sink capacity. The supplemental LED lighting increased the size of fruits in the middle and distal positions of the truss, resulting in a more even size for each fruit in the truss. Diurnal analysis of fruit growth showed that fruits grew more quickly during the night on the plants receiving LED light than on unsupplemented control plants. This faster fruit growth during the night was related to an increased root pressure. The LED treatment also increased the xylem levels of the phytohormone jasmonate. Supplemental LED inter-lighting increased tomato fruit weight without affecting the total soluble solid contents in fruits by increasing the total assimilates available for fruit growth and by enhancing root activity through an increase in root pressure and water supply to support fruit growth during the night.